Evaluative altmetrics: is there evidence for its application to research evaluation? - Arroyo-Machado, Wenceslao; Torres-Salinas, Daniel (Frontiers in Research Metrics and Analytics, 2023)
Altmetrics have proved their potential for the study of scientific communication on social media. However, although their research has been progressing towards a valuable approach for studying the diverse interactions produced around science, no progress has been made in their application for research evaluation. In this paper, a methodological proposal is made to apply altmetrics in the evaluation of researchers, using as a case study the production of the Environment/Ecology ESI field authored by researchers at the University of Granada. Using Twitter as a reflection of social attention, news outlets as media and Wikipedia as educational, the mentions of these three media and the actors involved are explored in their corresponding media to contextualise them using different metrics. The type of audience, its local impact, the engagement produced around the mention and the profile of the actor are the dimensions analysed to ultimately provide dashboards that offer a clear picture of the various social attentions at the author level.